ASSESSING PERFORMANCE IN FORENSIC HAIR EXAMINATION: A REVIEW - D'Orio, Eugenio; Calabrese, Giuseppe; Lucanto, Chiara; Montagna , Paola (International Journal of Law in Changing World, 2023)
Forensic biological examination is a part of forensic science, which has the aims to identify biological matrix and stains on crime scenes or findings. Forensic biological examination is important for the identification of even the smallest biological samples and their attribution to a specific person, victim or suspect. During crime scene investigation hair is one of the biological samples that can be found and can lead the operators to identify the perpetrators. In fact, hair can be easily found on findings, both clothes and objects, near victims and/or in the area of the crime. The hairs functions of protection, sensing and thermal insulation make them strongly present in almost all human population, increasing the possibility to found them quite everywhere, also on crime scenes. Microscopic analysis of the human hairs can be used to make a comparative analysis on suspects, focus the attention on pretty well-known morphological characteristics such as: medulla; scales; cortex; cuticle and pigmentation. Furthermore, the bulb of human hair, found on crime scenes or on findings, can be used in forensic genetics examination to reach a DNA matching between hairs and suspect or victim. In fact, only within the bulb there are traces of nucleated cells that let the operators to extract DNA and carry out a genetic profile. The aim of this research is to cross-compare multiple knowledge from different research papers on forensic hair examination in order to assess the evolution of the study and technology in this field and for assess new perspective of research and forensic applications.